Design and synthesis of a new topical agent for halting blood loss rapidly: a multimodal chitosan-gelatin xerogel composite loaded with silica nanoparticles and calcium - Patil, Gokul; Torris, Arun; Suresha, P. R.; Jadhav, Sachin; Badiger, V. Manohar; Ghormade, Vandana (Colloids and Surfaces B-Biointerfaces, 2021)
Uncontrolled hemorrhage often causes death during traumatic injuries and halting exsanguination topically is a challenge. Here, an efficient multimodal topical hemostat was developed by (i) ionically crosslinking chitosan and gelatin with sodium tripolyphosphate for (ii) fabricating a robust, highly porous xerogel by lyophilization having 86.7 % porosity, by micro-CT and large pores similar to 30 mu m by SEM (iii) incorporating 0.5 mg synthesized silica nanoparticles (SiNPs, 120 nm size, -22 mV charge) and 2.5 mM calcium in xemgel composite that was confirmed by FTIR analysis with peaks at 3372, 986 and 788 cm(-1), respectively. XPS analysis displayed the presence of SiNPs (Si2p peak for silicon) and calcium (Ca2p1, Ca2p3 transition peaks) in the composite. Interestingly, in silico percolation simulation for composite revealed interlinked 800 mu m long-conduits predicting excellent absorption capacity and validated experimentally (640 % of composite dry weight). The composite achieved >16-fold improved blood clotting in vitro than commercial Celox and Gauze through multimodal interaction of its components with RBCs and platelets. The composite displayed good platelet activation and thrombin generation activities. It displayed high compressive strength (2.45 MPa) and withstood pressure during application. Moreover, xerogel composite showed high biocompatibility. In vivo application of xerogel composite to lethal femoral artery injury in rats achieved hemostasis (2.5 min) significantly faster than commercial Celox (3.3 min) and Gauze (4.6 min) and was easily removed from the wound. The gamma irradiated composite was stable till 1.5 yr. Therefore, the xerogel composite has potential for application as a rapid topical hemostatic agent.
Keywords: Hemostatic; Polymer; silica nanoparticles; Xerogel